Sources of financing for increasing the competitiveness of the food Industry in Azerbaijan - Farid Babayev (Наукові горизонти, 2023)
The state policy of the government of Azerbaijan is aimed at the sectoral diversification of the economy of the country, in which the food industry occupies a significant place. Since for a long time there has been a raw materials-based model of the economy in Azerbaijan, investment funds have not been not directed to increase the competitiveness of the food industry in order to operate successfully in the global market. The main aim of the research is to investigate the opportunity of using various sources of financing, which are required to improve the Azerbaijani food industry competitivity. The methods of summary and grouping, analysis, synthesis, induction, deduction, were used in order to reach the goal. It was shown that the food industry in the state could be improved by increasing the climate investment and the share of outside and joint financing sources. During the research conducted it was determined that over the past 15 years, the government of Azerbaijan has implemented more than 70 national and industry specific programs. The work separately points out the State Programs I and II on the economic and social development of the regions, which were introduced in the period from 2004 to 2013. For increasing the food sector competitivity in Azerbaijan, additional financial resources, which reached $65 billion in 2012, were attracted in the country; loans to strengthen the competitiveness of the food industry increased by 9.7 times in the period between 2006 and 2021, and the investment volume will exceed $3 billion in the result. The positive impact of the measures, which were taken, was reflected in the creation of additional 1.2 million jobs in the food industry in the Republic of Azerbaijan. The study results showed that internal sources were the largest share in the financing of the food industry in the country, while the due attention was not paid to the development of international cooperation aimed at increasing external and joint sources of financing. The practical significance of the results of the study presented in this article lies in its providing of the basis for subsequent areas of study of the topic under consideration, as well as for the development of state programs on the improving of the food sector in Azerbaijan